Comparison of structure and numbers of genes among cereals - XUE Qing-zhong (浙江大学学报. 农业与生命科学版)
This review describes the current state of knowledge regarding cereal genome structure. Annotation based on the sequencing of long genomic segments from cereals and the whole-genome analyses of Arabidopsis and rice, suggests that a mosaic structure consisting of recombinationally active gene-rich islands that are separated by blocks of high-copy DNA. Macrocolinearity within the cereals is conserved. By analysing the gene order of the Sh2/A1 orthologous region of maize, rice, sorghum, wheat, and barley, the Sh2 and A1 homologs are separated by 20 kb in rice and sorghum and by 140 kb in maize. The synteny in the Sh2/A1 region is interrupted by a break between the X1 and X2 genes in the triticeae. The colinear between A1 and X2 genes remains in homeologous chromosomes as in other grasses, but that between Sh2 and X1 orthologs were translocated to a nonhomeologous chromosome. Through three forms of duplication, i.e. polyploidization, segmental duplication, and local gene amplification, increases the number of paralogous gene sequences found in plants. At the level of individual genes, microcolinearity is frequently disrupted. Preliminary evidence from comparative analysis of sequenced orthologous genomic segments suggests that local gene amplification and translocation within a plant genome may be linked in some cases.